Pemberian Pre-Test Dan Post-Test Terhadap Kader Kesehatan Pada Pemberdayaan Kader Di Puskesmas Palapa Kota Bandar Lampung : The Effect of Giving Pre-Test and Post-Test on Health Cadres in Empowering Cadres at the Palapa Health Center in Bandar Lampung CityPengaruh - Indah Ismalia; Novita Sari; Rossy Meliyana; Vera Yulyani; Prima Dian Furqoni; Dina Dwi Nuryani (LPPM Institut Studi Islam Sunan Doe, 2022)
ISPA is the main cause of morbidity and mortality from infectious diseases in the world. ARI is still the main cause of infant and toddler mortality in Indonesia. From several SKRT results it is known that 80 to 90% of all cases of ISPA deaths are caused by pneumonia. This Field Practice is intended so that cadres are able and willing to carry out their duties, namely helping the community to be able to help themselves and participate actively in the field of health. They need to be prepared and developed. The method used in this research is a quantitative research method. The research design uses an analytic descriptive design. The results of the participant's pre-test and post-test scores, namely the pre-test score has an average (mean) of 165.5 and the post-test value data has an average increase of 220. These changes indicate that the Health Cadres experienced an increase in knowledge after participating in Cadre Empowerment activities. It can be proven that the material given to the participants during the training session is proven to be able to increase the knowledge and understanding of the participants significantly, due to a significant increase in score.